2021
DOI: 10.3389/fpsyg.2021.738959
|View full text |Cite
|
Sign up to set email alerts
|

Applying Control-Value Theory and Unified Theory of Acceptance and Use of Technology to Explore Pre-service Teachers’ Academic Emotions and Learning Satisfaction

Abstract: Academic emotions refer to the emotions related to achievement activities or outcomes. Academic emotions are directly related to learning performance and have been recognized as critical to learners’ learning satisfaction and learning effectiveness in the online learning context. This study aimed to explore the relationship between academic emotions and learning satisfaction and their underlying mechanisms in massive open online courses (MOOCs) learning context using mediation models. This study adhered to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 63 publications
2
22
1
Order By: Relevance
“…(1) Performance Expectancy (PE) Performance Expectancy is defined as the degree to which individuals believe that new technology helps to improve their job performances. According to Venkatesh (Venkatesh et al, 2003), a significant positive effect of PE was observed on a person's intention to adopt new technology (Wu et al, 2021). This indicated that the notion of this variable emphasized the extent to which frontline primary and secondary school teachers believed (Venkatesh et al, 2012).…”
Section: The Situation Of Interactive Whiteboard In Remote and Rural ...mentioning
confidence: 95%
“…(1) Performance Expectancy (PE) Performance Expectancy is defined as the degree to which individuals believe that new technology helps to improve their job performances. According to Venkatesh (Venkatesh et al, 2003), a significant positive effect of PE was observed on a person's intention to adopt new technology (Wu et al, 2021). This indicated that the notion of this variable emphasized the extent to which frontline primary and secondary school teachers believed (Venkatesh et al, 2012).…”
Section: The Situation Of Interactive Whiteboard In Remote and Rural ...mentioning
confidence: 95%
“…In mobile apps, perceived performance captures behavioral intentions, functional intentions, and adoptions ( Chipeva et al, 2018 ). People are more receptive when new technology is readily available and simple to use ( Wu et al, 2021 ). In cell phone services, perceived performance is an important predictor ( Rita et al, 2018 ).…”
Section: Formulation Of Hypothesesmentioning
confidence: 99%
“…More recently, certain studies have emerged that provided inconsistent findings. No significant relationship was found between learners' achievement emotions and their engagement in online learning (Wu et al, 2021a). The inconsistent findings were also supported by Wang et al (2022).…”
Section: Engagementmentioning
confidence: 89%
“…Current literature has paid attention to the effects of achievement emotions on online learning satisfaction. The existing research reported that achievement emotions exerted a negative (Artino, 2009), positive (Golding and Jackson, 2021), and even non-significant (Wu et al, 2021a) influence on online learning satisfaction. In conclusion, these studies showed that the effects of achievement emotions on satisfaction were complex.…”
Section: Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation